MANAGING RISK IN OFFSHORE SYSTEMS DEVELOPMENT. - Sakthivel, S. (Communications of the ACM, 2007)
The article discusses benefits of managing risk in offshore computer software systems development. While outsourcing computer engineers provides benefits in terms of low-cost labor, these benefits can often be outweighed by missed deadlines, dissatisfied users, and a failure to reduce development costs. To manage these risks, organizations can create standardized documentation, deliver clear goals to the outsourced workers, establish trust between organizations, and use a subsidiary to manage the company.